PERAN APOTEKER DALAM MENINGKATKAN HASIL PENGOBATAN PASIEN DIABETES TIPE 2: TINJAUAN INTERVENSI DI FASILITAS KESEHATAN INDONESIA - Amelia, Riza; Hermanto, Faizal (Jurnal Buana Farma, 2025)
Type 2 diabetes mellitus is one of the chronic diseases with low treatment success rates. This article aims to assess the effectiveness of pharmacist interventions in improving treatment outcomes for patients with type 2 diabetes. The research method used is a narrative review through searching the PubMed and Google Scholar databases. This study reviewed journals from the years 2015 to 2025, resulting in 791 articles. A total of 11 articles met the inclusion criteria. The results of the research indicate that pharmacist interventions can significantly improve treatment outcomes, including increased adherence, improved quality of life for patients with type 2 diabetes, and achievement of stable glucose levels.